A design and preparation method of titanium alloy superhydrophobic surface based on response surface methodology

By designing and preparation methods based on the titanium alloy ultra -hydrophobic surface design based on the response surface method, the problem of lack of mechanical performance and abrasion resistance in the existing technologies in the surface of the titanium alloy surface is built on the surface of the titanium alloy. The design and production of ultra -hydrophobic microstructure expanded the application field.

CN118981907BActive Publication Date: 2025-01-24JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411472599.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

When existing superhydrophobic materials build micro-nano structures on the surface of titanium alloys, their mechanical properties and wear resistance are insufficient, and it is difficult to effectively build superhydrophobic structures on complex curved surfaces, resulting in failure of superhydrophobic properties.

Method used

The titanium alloy ultra -hydrophobic surface design and preparation method based on the response surface method is adopted, and micro -structures with excellent ultra -hydrophobic properties are optimized by 3D metal printing, ultrasonic fluoride treatment, and response surface method.

Benefits of technology

The mechanical properties and abrasion resistance of the micro -structure of the ultra -hydrophobic surface are improved, and the ultra -hydrophobic performance is avoided due to poor coating force, and the design and production of ultra -hydrophobic micro -structures is achieved on the complex curved surface, expanding the application field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118981907B_ABST
    Figure CN118981907B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium alloy super-hydrophobic surface design and preparation method based on response surface methodology, belonging to the field of super-hydrophobic materials. The response surface methodology of the present invention tests the interaction of the super-hydrophobic microstructure of TC4 alloy, and obtains the microstructure that is most conducive to improving the super-hydrophobic performance by establishing a prediction model and optimizing the microstructure parameters, and provides more excellent microstructure parameters for the production of the surface microstructure directly formed by additive manufacturing. And the microstructure constructed by additive manufacturing technology has more excellent mechanical properties and wear resistance compared with traditional processing methods, and at the same time, there is no need to worry about the failure of super-hydrophobic performance caused by the poor bonding force of the super-hydrophobic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of super-hydrophobic materials, and in particular relates to a design and preparation method of a super-hydrophobic surface of a titanium alloy based on a response surface methodology. Background Art

[0002] Superhydrophobic materials have attracted widespread attention in the fields of aerospace, marine antifouling, shipbuilding, biomedicine, etc. due to their unique self-cleaning, low friction, corrosion resistance, anti-icing and anti-pollution properties. At present, superhydrophobic materials are mainly achieved by constructing surface micro-nano structures and reducing the surface energy of the substrate. When constructing micro-nano structures on the surface of titanium alloys, most of them are achieved by laser processing, electrochemical deposition and other methods. However, since the surface microstructure constructed by laser processing is usually only tens of microns or even smaller, it is often replaced by sacrificing its mechanical properties and wear resistance, which can easily lead to surface microstructure failure after wear, and it is not easy to construct micro-nano structures in some complex curved surface application scenarios, which limits its application field. Depositing superhydrophobic coatings on the surface of metal substrates by electrochemical deposition methods or constructing rough micro-nano structures has poor bonding between the coating and the substrate. After the coating bonding is destroyed, the superhydrophobic performance will also fail.

[0003] Moreover, the design of superhydrophobic structures on complex curved surfaces is also quite different from that on ordinary flat surfaces. The superhydrophobic effect obtained by directly designing superhydrophobic microstructures on complex curved surfaces is not ideal. Therefore, there is currently no better solution for the design of superhydrophobic surface structures on complex curved surfaces.

[0004] Therefore, a new solution is needed that can optimize various super-hydrophobic surface microstructures and produce super-hydrophobic surface workpieces with better mechanical properties and wear resistance. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology comprises the following steps:

[0008] Step 1: Design according to requirements, determine the structure distribution and size of the super-hydrophobic surface and perform three-dimensional modeling;

[0009] Step 2: Use metal additive manufacturing equipment to perform 3D metal printing to produce TC4 alloy samples with different microstructure parameters;

[0010] Step 3, subjecting the produced TC4 alloy sample to ultrasonic fluorination treatment to reduce the surface energy of the TC4 alloy;

[0011] Step 4, measuring the liquid contact angle of the sample after ultrasonic fluorination;

[0012] Step 5, using the response surface method to establish a nonlinear mapping relationship between microstructure height, staggered angle, spacing and liquid contact angle, establish a wettability prediction model, optimize the microstructure parameters, and obtain microstructure parameters with excellent superhydrophobic properties;

[0013] Step six: Based on the obtained microstructure parameters, further design and production of the product is carried out.

[0014] Furthermore, in the step 1, the super-hydrophobic surface structure selected is the lotus leaf surface, and three-dimensional modeling is performed according to the size and distribution of the micro-nano structure on the lotus leaf surface.

[0015] Furthermore, in step 2, the 3D metal printing technology uses SLM printing, the selected metal is TC4 alloy, and the specific method of using SLM printing is:

[0016] The particle size of the TC4 alloy powder used was 35 μm. Under argon atmosphere, a printing strategy with a laser power of 180 W, a scanning speed of 800 mm / s, a scanning interval of 0.06 mm, and a layer thickness of 0.02 mm was adopted to print TC4 alloy samples with different microstructure parameters.

[0017] Furthermore, in step three, the specific method of ultrasonic fluorination treatment is: dissolving 0.1wt% 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution in alcohol, placing the sample therein, and taking it out after ultrasonic treatment in an ultrasonic cleaning instrument for 10 minutes.

[0018] Furthermore, in step 4, the specific method for measuring the sample liquid contact angle is: placing the sample on the substrate of the liquid contact angle measuring instrument, dropping 5 μL of liquid droplets on the sample surface through a needle, and then using the five-point method to fit and measure the liquid contact angle.

[0019] Furthermore, in step 5, the wettability prediction model established by the response surface methodology is:

[0020] ;

[0021] Where Z is the liquid contact angle of the sample, A is the microstructure height, B is the microstructure staggered angle, and C is the microstructure spacing.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] This scheme tests the interaction of TC4 alloy superhydrophobic microstructure based on response surface methodology, and obtains the microstructure that is most conducive to improving superhydrophobic performance by establishing a prediction model and optimizing microstructure parameters, providing more excellent microstructure parameters for the production of additive manufacturing direct molding surface microstructures;

[0024] The microstructure constructed by additive manufacturing technology in this solution has better mechanical properties and wear resistance than traditional processing methods. At the same time, there is no need to worry about the failure of super-hydrophobic performance due to poor bonding strength of super-hydrophobic coating;

[0025] This solution combines additive manufacturing technology with the construction of super-hydrophobic surface microstructures, giving the microstructure the ability to be formed on complex curved surfaces, making it possible to design and produce super-hydrophobic microstructures on some complex curved surfaces, expanding its application areas. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a technical roadmap for the design method of bionic super-hydrophobic surface of titanium alloy in additive manufacturing based on response surface methodology in the present invention.

[0027] Figure 2 Flow chart of sample preparation in the present invention.

[0028] Figure 3 This is a diagram showing the interaction between microstructure parameters and surface wettability in the embodiment.

[0029] Figure 4 It is a relationship diagram between the predicted value and the actual value of the wettability prediction model in the embodiment.

[0030] Figure 5 This is a graph of the liquid contact angle measured for the sample after the microstructure parameters are optimized in the embodiment.

[0031] In the figure: 1. SLM metal additive manufacturing equipment; 2. TC4 alloy powder; 3. Papillary microstructure surface; 4. Anhydrous ethanol solution; 5. 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution; 6. Fluorination treatment solution; 7. Ultrasonic cleaning instrument. DETAILED DESCRIPTION

[0032] In order to solve the problems in the prior art that the super-hydrophobic surface micro-nano structure has poor mechanical properties, poor wear resistance, weak coating bonding, easy failure of super-hydrophobic performance and limited application in complex curved surfaces, the present invention provides a new solution that can optimize the design of the super-hydrophobic surface microstructure and effectively improve the mechanical properties and wear resistance of the microstructure, and the design and preparation scheme thereof includes the following steps:

[0033] Step 1: Design according to requirements, determine the structure distribution and size of the super-hydrophobic surface and perform three-dimensional modeling;

[0034] Step 2: Use metal additive manufacturing equipment to perform 3D metal printing to produce TC4 alloy samples with different microstructure parameters;

[0035] Step 3, subjecting the produced TC4 alloy sample to ultrasonic fluorination treatment to reduce the surface energy of the TC4 alloy;

[0036] Step 4, measuring the liquid contact angle of the sample after ultrasonic fluorination;

[0037] Step 5, using the response surface method to establish a nonlinear mapping relationship between microstructure height, staggered angle, spacing and liquid contact angle, establish a wettability prediction model, optimize the microstructure parameters, and obtain microstructure parameters with excellent superhydrophobic properties;

[0038] Step six: Based on the obtained microstructure parameters, further design and production of the product is carried out.

[0039] The present invention is further described below in conjunction with specific embodiments.

[0040] In this embodiment, the super-hydrophobic surface microstructure selected is the papillary microstructure on the surface of the lotus leaf.

[0041] like Figure 1 and Figure 2 As shown, the specific steps are as follows:

[0042] Step 1: According to the design requirements, determine the distribution and size of the lotus leaf papillary microstructure and perform three-dimensional modeling;

[0043] Step 2, using SLM metal additive manufacturing equipment 1, through 3D metal printing, printing out TC4 alloy papillary microstructure surface 3 samples with different microstructure parameters;

[0044] Step 3, subjecting the printed sample to ultrasonic fluorination treatment for 10 minutes to reduce the surface energy of the TC4 alloy;

[0045] Step 4, measuring the liquid contact angle of the sample obtained after ultrasonic fluorination;

[0046] Step 5, using the response surface method to establish a nonlinear mapping relationship between microstructure height, staggered angle, spacing and liquid contact angle, establish a wettability prediction model, optimize the microstructure parameters, and obtain microstructure parameters with excellent superhydrophobic properties;

[0047] In step one, three-dimensional modeling is performed based on the size and distribution of the micro-nanostructure on the lotus leaf surface, and after proportional enlargement, the size of the lotus leaf-like papillary microstructure is determined to be 0.3-0.7 mm in height, 30-90° in staggered angle, and 0.4-0.6 mm in spacing.

[0048] In step 2, the specific method of SLM printing is as follows: the particle size of the TC4 alloy powder 2 used is about 35 μm, and in an argon atmosphere, a printing strategy with a laser power of 180 W, a scanning speed of 800 mm / s, a scanning spacing of 0.06 mm, and a layer thickness of 0.02 mm is adopted to print out TC4 alloy papillary microstructure surface 3 samples with different microstructure parameters.

[0049] In step three, the specific method of ultrasonic fluorination treatment is: dissolve 0.1wt% 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution 5 in anhydrous ethanol solution 4, place the sample obtained in step two therein, and take it out after ultrasonic treatment in an ultrasonic cleaning instrument 7 for 10 minutes.

[0050] In step 4, the specific method for measuring the liquid contact angle of the sample is: placing the sample on the substrate of the liquid contact angle measuring instrument, dropping a 5 μL droplet on the sample surface through a needle, and then using the five-point method to fit and measure the liquid contact angle.

[0051] The papillary microstructure surface 3 of each different parameter in the sample was measured, and the test results are shown in Table 1 below:

[0052] Table 1

[0053] Serial number Height (mm) Stagger angle (°) Microstructure spacing (mm) Contact angle (°) 1 0.5 60 0.5 151.113 2 0.5 60 0.5 151.125 3 0.5 90 0.6 143.893 4 0.5 60 0.5 151.214 5 0.7 60 0.4 132.769 6 0.7 90 0.5 147.358 7 0.7 30 0.5 140.885 8 0.3 60 0.6 137.07 9 0.5 60 0.5 151.928 10 0.5 90 0.4 134.397 11 0.5 30 0.4 138.734 12 0.3 90 0.5 135.354 13 0.5 30 0.6 145.528 14 0.5 60 0.5 150.945 15 0.3 30 0.5 143.659 16 0.3 60 0.4 135.15 17 0.7 60 0.6 151.113

[0054] According to the visualization model diagram of the interaction between the microstructure parameters and the surface wettability in the above table, Figure 3 shown.

[0055] After the test is completed, the data is input into step five to establish a prediction model and optimize various parameters of the microstructure.

[0056] In step 5, the wettability prediction model established by response surface methodology is:

[0057] ;

[0058] Where Z is the liquid contact angle of the sample, A is the microstructure height, B is the microstructure staggered angle, and C is the microstructure spacing.

[0059] According to the prediction model, the relationship between the model prediction value and the actual value is as follows: Figure 4As shown in the figure, the horizontal and vertical axes represent the predicted value and actual value of the liquid contact angle respectively. The closer the two values ​​are to the center line, the closer the value predicted by the model is to the actual value, and the higher the fit between the model and the actual value. From the data in the figure, it can be seen that the points corresponding to the actual value of the liquid contact angle and the predicted value obtained by the above prediction model are closely clustered around the diagonal line, and the distribution is also relatively balanced, which shows that the constructed model has excellent fit and can provide accurate predictions.

[0060] The prediction model based on step 5 is used to predict and optimize the surface microstructure of TC4 alloy. The height of the optimized surface microstructure of TC4 alloy is 0.55mm, the staggered angle is 67.44°, the spacing is 0.54mm, and the predicted liquid contact angle is 152.215°. The actual test picture of the sample produced again is as follows Figure 5 As shown, the actual liquid contact angle is measured to be 152.395°, which is within the error range and confirms that it has good superhydrophobic properties.

[0061] It should be noted that it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any figure mark in the claims should not be regarded as limiting the claims involved.

[0062] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A design and preparation method for a titanium alloy super-hydrophobic surface based on response surface methodology, characterized in that: The steps include: Step 1: Design according to requirements, determine the structure distribution and size of the super-hydrophobic surface and perform three-dimensional modeling; Step 2: Use metal additive manufacturing equipment to perform 3D metal printing to produce TC4 alloy samples with different microstructure parameters; Step 3, subjecting the produced TC4 alloy sample to ultrasonic fluorination treatment to reduce the surface energy of the TC4 alloy; Step 4, measuring the liquid contact angle of the sample after ultrasonic fluorination; Step 5, using the response surface method to establish a nonlinear mapping relationship between microstructure height, staggered angle, spacing and liquid contact angle, establish a wettability prediction model, optimize the microstructure parameters, and obtain microstructure parameters with excellent superhydrophobic properties; Step six: Based on the obtained microstructure parameters, further design and production of the product is carried out.

2. The method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology according to claim 1, characterized in that: In the step 1, the super-hydrophobic surface structure selected is the lotus leaf surface, and three-dimensional modeling is performed according to the size and distribution of the micro-nano structure on the lotus leaf surface.

3. The method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology according to claim 1, characterized in that: In step 2, the 3D metal printing technology uses SLM printing, the selected metal is TC4 alloy, and the specific method of using SLM printing is as follows: The particle size of the TC4 alloy powder used was 35 μm. Under argon atmosphere, a printing strategy with a laser power of 180 W, a scanning speed of 800 mm / s, a scanning interval of 0.06 mm, and a layer thickness of 0.02 mm was adopted to print TC4 alloy samples with different microstructure parameters.

4. The method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology according to claim 1, characterized in that: In the step 3, the specific method of ultrasonic fluorination treatment is: dissolving 0.1wt% 1H,1H,2H,2H-perfluorodecyltriethoxysilane solution in alcohol, placing the sample therein, and taking it out after ultrasonic treatment in an ultrasonic cleaning instrument for 10 minutes.

5. The method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology according to claim 1, characterized in that: In step 4, the specific method for measuring the liquid contact angle of the sample is: placing the sample on the substrate of the liquid contact angle measuring instrument, dropping 5 μL of liquid droplets on the sample surface through a needle, and then using the five-point method to fit and measure the liquid contact angle.

6. The method for designing and preparing a super-hydrophobic surface of a titanium alloy based on response surface methodology according to claim 1, characterized in that: In step 5, the wettability prediction model established by the response surface method is: ; Where Z is the liquid contact angle of the sample, A is the microstructure height, B is the microstructure staggered angle, and C is the microstructure spacing.

Citation Information

Patent Citations

  • Metal-based wetting surface structure design method based on biological coupling mechanism

    CN106971018A

  • Metal super-hydrophobic surface preparation method and application thereof

    CN110468415A